Application Of Silver Nanoparticles On Experimental Wound Infection Of Pseudomonas aeruginosa In Rats - Wijdan Abdulghani Saleh Alhammadi; Donia Suad Shakor; Parzhin Sardar Mohammed; Asmaa Jamal Mohammed; Afaf Saud Hussein; Mohannad Hamid Jasim; Mariam Ahmed Kamal (International Journal of Antibiotics, 2024)
This study aimed to evaluate the application of silver nanoparticles on experimental wound infection of Pseudomonas aeruginosa in rats. Infected patients at a private hospital in Baghdad had fifty swab samples taken from their wounds and burns (25 samples in total). These swabs were cultured on primary medium and then routine bacteriological tests were done for identification. Molecular confirmation of bacteria was done by using 16S rRNA gene. The research found that out of 25 swabs taken from wound and burn regions, 15 (60%) and 16 (64%), respectively, of P. aeruginosa tested positive for the 16S rRNA gene. The bacterial suspension was applied to each wound bed after twenty-one rats were sedated and full-thickness skin wounds were made on their backs. Wound infection was evaluated by counting the total number of bacteria in the wound, and the healing process was seen under a microscope. The following treatments were given topically to the wound bed in all groups: G1 without treatment, G2 with bacterial infection but no therapy, and G3 with bacterial infection and subsequent treatment with 10 µL of AgNPs (0.04 mg/cm2). There is a tight relationship between the percentage of wound contraction in the AgNPs group and the other groups. The concentration of surface bacteria was shown to be lower in all groups treated with AgNPs by day 12 when compared to G2. The numbers of deep skin bacteria were significantly lower in the AgNPs group compared to the G2 group at any time point (P .
Keywords: 16S rRNA; Nanoparticle; P. aeruginosa; PCR; Wound infection